The Runaways - Bhutto, Fatima (New Dehli; Penguin Random House, 2019)
Anita lives in Karachi's biggest slum. Her mother is a maalish wali, paid to massage the tired bones of rich women. But Anita's life will change forever when she meets her elderly neighbour, a man whose shelves of books promise an escape to a different world.
Keywords: Asian Fiction